Uma interface para usuários novatos do sistema Patplus - Cristina Duarte Murta (1990)
This thesis presents a human-computer interface f a r novice users of PATPLUS, a f u l l - t e x t information retrieval system f o r microcamputer5. The design of t h e interface was based on a study of the literature on human-computer interfaces and interactive systems development. The main concepts and some aspects of dialogue design, interaction techniques and user types are described.